COVID-19 Patients Upregulate Toll-like Receptor 4-mediated Inflammatory Signaling That Mimics Bacterial Sepsis - Sohn, Kyung Mok; Lee, Sung-Gwon; Kim, Hyeon Ji; Cheon, Shinhyea; Jeong, Hyeongseok; Lee, Jooyeon; Kim, In Soo; Silwal, Prashanta; Kim, Young Jae; Paik, Seungwha; Chung, Chaeuk; Park, Chungoo; et al. (Journal of Korean medical science, 2020)
Observational studies of the ongoing coronavirus disease 2019 (COVID-19) outbreak suggest that a 'cytokine storm' is involved in the pathogenesis of severe illness. However, the molecular mechanisms underlying the altered pathological inflammation in COVID-19 are largely unknown. We report here that toll-like receptor (TLR) 4-mediated inflammatory signaling molecules are upregulated in peripheral blood mononuclear cells (PBMCs) from COVID-19 patients, compared with healthy controls (HC). A total of 48 subjects including 28 COVID-19 patients (8 severe/critical vs. 20 mild/moderate cases) admitted to Chungnam National University Hospital, and age/sex-matched 20 HC were enrolled in this study. PBMCs from the subjects were processed for nCounter Human Immunology gene expression assay to analyze the immune related transcriptome profiles. Recombinant proteins of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) were used to stimulate the PBMCs and monocyte-derived macrophages, and real-time polymerase chain reaction was performed to quantify the mRNA expressions of the pro-inflammatory cytokines/chemokines. Among the most highly increased inflammatory mediators in severe/critically ill patients, S100A9, an alarmin and TLR4 ligand, was found as a noteworthy biomarker, because it inversely correlated with the serum albumin levels. We also observed that recombinant S2 and nucleocapsid proteins of SARS-CoV-2 significantly increased pro-inflammatory cytokines/chemokines and S100A9 in human primary PBMCs. These data support a link between TLR4 signaling and pathological inflammation during COVID-19 and contribute to develop therapeutic approaches through targeting TLR4-mediated inflammation.